2017
DOI: 10.1371/journal.pntd.0005403
|View full text |Cite
|
Sign up to set email alerts
|

Endomyocardial involvement in asymptomatic sub-Saharan immigrants with helminth-related eosinophilia

Abstract: BackgroundAmong immigrants of sub-Saharan origin, parasitic infection is the leading cause of eosinophilia, which is generally interpreted as a defense mechanism. A side effect of the inflammatory mediators released by eosinophils is damage to host organs, especially the heart. The main objectives of this study were to i) assess cardiac involvement in asymptomatic sub-Saharan immigrants with eosinophilia, ii) relate the presence of lesions with the degree of eosinophilia, and iii) study the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Four studies examined the associations of helminths with non-atherosclerotic cardiovascular disease, defined in these studies as myocardial injury, myocardium lipid deposits, cardiac hypertrophy, eosinophilic myocarditis, or other endomyocardial manifestations of eosinophilia that may be related to helminth infections [46,[96][97][98]. None of these studies investigated the subsequent effects of anthelmintic treatment on outcomes of non-atherosclerotic cardiovascular disease (S8 Table ).…”
Section: Helminths and Non-atherosclerotic Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Four studies examined the associations of helminths with non-atherosclerotic cardiovascular disease, defined in these studies as myocardial injury, myocardium lipid deposits, cardiac hypertrophy, eosinophilic myocarditis, or other endomyocardial manifestations of eosinophilia that may be related to helminth infections [46,[96][97][98]. None of these studies investigated the subsequent effects of anthelmintic treatment on outcomes of non-atherosclerotic cardiovascular disease (S8 Table ).…”
Section: Helminths and Non-atherosclerotic Cardiovascular Diseasementioning
confidence: 99%
“…Cross-sectional associations between helminth infections and non-atherosclerotic cardiovascular disease. Of these 4 studies, 2 showed some increase in non-atherosclerotic cardiovascular disease [96,98], 1 reported less non-atherosclerotic cardiovascular disease [46], and 1 found no relationship between non-atherosclerotic cardiovascular disease [97] and helminth infections.…”
Section: Helminths and Non-atherosclerotic Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation